A Research on Developmental Characteristics of Children With Language Delay in Zhejiang Province, China - Dan Yao; Dan Yao; Yan Zeng; Yan Zeng; Minjie Gao; Minjie Gao; Jiyang Shen; Jiyang Shen; Jianying Zhan; Jianying Zhan; Zhengyan Zhao; Zhengyan Zhao (Frontiers Media S.A., 2020)
Study Design: We used Sign-significant relations (S-S) to assess the developmental characteristics of 1- to 4-year-old children with language delays in Zhejiang Province and to provide scientific basis for early clinical detection and comprehensive intervention.Methods: A total of 1,113 children among the ages of 1 and 4 who complained of poor language skills were assessed in language competence using S-S. These children diagnosed with language delays were divided into six groups, with each group having an age difference of 6 months. The developmental characteristics of each group were described and analyzed.Results: (1) Children from the age of 18 to 36 months were most likely to be affected by language problems, while boys were more susceptible than girls in each group. (2) There was no significant difference in the proportion of children with poor communication attitude among the groups. (3) The older the group, the higher the proportion of basic learning ability abnormality. The cutoff age for qualitative leap in the proportion of basic learning abilities was 2 years old. (4) With the increase of age, the proportion of abnormal language comprehension in each group increased gradually. The cutoff age for qualitative leap in the proportion of language comprehension was 1.5 and 2 years old.Conclusion: Language delays usually occur in children around the age of two, and as the children get older, in addition to expression of language abilities, they are more likely to have abnormal language comprehensive abilities and abnormal basic learning abilities. Based on the clinical research, we must take seriously the early screenings for this age group and conduct intervention training as soon as possible.